The Lengyel Culture in Northwestern Croatia - Težak-Gregl, Tihomila (Array, 1998)
The article brings the most recent results of the archaeological excavations in Northwestern Croatia which have revealed the existance of a new, regional type of the endneolithic Lengyel cultural complex.